2011
DOI: 10.5513/jcea01/12.4.986
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of microbial biomass carbon and respiration activities in arable soil and pasture grassland soil

Abstract: The aim of our work was to survey and state the representative values and range of the microbial biomass carbon (C mic ) and microbial respiration activities in arable soils of three types (Chernozem, Luvisol, Planosol) and in pasture grassland soil (Cambisol). In arable soils no significant differences between the soil types were found concerning the content of C mic . Way of soil use significantly influenced C mic with higher values on pasture grassland soil. In Cambisol, a relatively strong relationships b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
(27 reference statements)
3
10
0
Order By: Relevance
“…This parameter shows the highest values on the site which is localized at the centre of peatbog, where carbon mineralization is very fast and decreases with increasing depth. These results agree to those of other authors (Maková et al 2011;Klose et al 2004), and from various types of ecosystems.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…This parameter shows the highest values on the site which is localized at the centre of peatbog, where carbon mineralization is very fast and decreases with increasing depth. These results agree to those of other authors (Maková et al 2011;Klose et al 2004), and from various types of ecosystems.…”
Section: Resultssupporting
confidence: 94%
“…Soil biological indices were positively correlated with soil organic carbon, while they were only negatively correlated with soil reaction measured in this study. Similar findings by other authors (Gömöryová et al 2009;Maková et al 2011) showed a very close relationship between chemical and biological soil parameters. Wide variations in the values of soil pH cause changes in physical and chemical soil properties, and thus, significantly influence microbial carbon and mineralization of soil organic matter.…”
Section: Resultssupporting
confidence: 92%
“…On average 95% of the microbial biomass and activities were governed by the soil organic carbon, soil total nitrogen, water holding capacity, soil aggregates, porosity and bulk density either positively or negatively (Table 4). The significant positive relations between the soil MBC and SOC agree with earlier reports by (Logahet al, 2010;Yang et al, 2010;Makova et al, 2011;Cheng et al, 2013;Bhuyanet al, 2013). This might be due to microbial biomass concentration depended on the organic matter availability to microbial activity , however, found no correlation between the biomass carbon and organic carbon.…”
Section: Discussionsupporting
confidence: 91%
“…The factors of soil forming process that contribute to the formation of individual soil types have also influenced the biomass of soil microorganisms, composition of microbial communities as well as their activities [17]. Reason for the variability of soil microbial activity is different forest and soil type.…”
Section: Discussionmentioning
confidence: 99%